Screening of key genes related to the prognosis of mouse sepsis - Chen, Muhu (Biosci Rep, 2020)
Sepsis is a common clinical disease with high mortality, and patients with sepsis have varied prognoses. Researchers need to explore the underlying mechanisms that determine the prognosis of sepsis. Hence, a mouse model was used to evaluate new potential prognostic markers of sepsis. Mice were randomly divided into low-dose group (n=3, lipopolysaccharides [LPS], 20 mg/kg) and high-dose group (n=3; LPS, 40 mg/kg). Total RNA was extracted from the peripheral blood of mice, and samples were then subjected to RNA sequencing. When complete data were normalized, the high-dose group and low-dose group were screened for differentially expressed genes (DEGs, log2FC ≥ 1 and q value ≤ 0.05). DEGs were analyzed by gene ontology enrichment, and potential core genes were screened using protein–protein interaction (PPI) network and weighted gene co-expression network analysis (WGCNA). Moreover, the survival data in GSE65682 were used to observe the correlation between core genes and prognosis. A total of 967 DEGs were identified in the low-dose group, of which 390 were up-regulated and 577 were down-regulated. These genes were mainly enriched in white blood cell activation, lymphocyte activation, immune system response etc. LCK, ZAP70, ITK, CD247, and DOCK2 were found at the core of PPI network, while WGCNA found that interferon-inducible protein 35 (IFI35), ITGB3, and mediator complex subunit 25 (MED25) may be potential core genes. It was demonstrated that CD247, DOCK2, IFI35, ITK, and LCK core genes were positively correlated with prognosis based on GSE65682. CD247, DOCK2, IFI35, ITK, LCK, and MED25 might be important targets affecting the prognosis of sepsis.